Developing critical reading behaviors through guided close reading of research articles - Jaya, Sinarman; Kusmiarti, Reni; Paulina, Yanti (Indonesian Journal of Educational Development (IJED), 2026)
The ability to construct well-reasoned arguments remains a challenge for many EFL undergraduates engaged in academic reading and writing. This study examines how guided close reading of research articles supports the development of critical reading behaviors and research-based academic writing. Using a mixed-methods design, the study was conducted in a Research in ELT course involving 24 fifth-semester EFL students selected through intact-class sampling. Data were collected through think-aloud protocols, reading logs, classroom observations, and two stages of academic writing drafts. Quantitative data were analyzed descriptively and through paired sample comparisons, while qualitative data were thematically coded to capture analytical, evaluative, and metacognitive reading behaviors. The findings indicate a shift from surface comprehension toward deliberate engagement with claims, evidence, assumptions, and reasoning. These changes were reflected in clearer argument structures and improved integration of evidence in students' writing. The study recommends integrating guided close reading into academic literacy courses to strengthen critical reading and research-based writing practices.